Immuno-engineering of drug delivery systems for modulation of inflammation - Nguyen, Tri Dang (Nanyang Technological University, 2021)
Systemic drug administration or extended release of anti-inflammatory therapeutics has been a clinically accepted treatment for chronic inflammatory diseases. However, this approach results in toxicity due to excessive drug administration compared to the dosage required by pathological conditions of the diseased sites. Hence, an unmet clinical need exists for a drug delivery system whose drug release profile matches the pathological requirements of patient-specific disease condition. Furthermore, adverse host immune response to biomaterial components of drug carriers also raises concerns about their success in clinical applications. This thesis aims to design immuno-compatible drug delivery systems which deliver therapeutic dosage correlating to the inflammation extent at diseased sites. Harnessing the knowledge of elevated protease activity at inflammatory diseased sites, we developed a modular hybrid hydrogel that releases anti-inflammatory drugs in a protease-responsive manner. The modular design of our system renders the hybrid hydrogel the versatility that allows for optimization of hydrogel formation, enzymatic cleavability, drug loading capacity, and drug release rate. Particularly, conjugating the drug to the hydrogel matrix was also explored as a drug-loading strategy to precisely control the triggered release mechanism in response to protease stimuli. Consequently, the protease-enhanced drug released from the hydrogel effectively inhibited in vitro TNF-α production by pro-inflammatory macrophages, suggesting its potential to manage local inflammation and alleviate drug-associated cytotoxicity. Importantly, the in vivo protease-triggered drug release was demonstrated using a newly established immuno-competent mouse model with varying severity of subcutaneous inflammation. Together, this thesis research demonstrates that our protease-triggered drug delivery hydrogel-based system could release drugs in response to subcutaneous inflammation in mice, suggesting its potential for immuno-compatible drug delivery to regulate inflammation in chronic diseases.